2008
DOI: 10.1002/ch.364
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis to manage distress related to medical procedures: a meta‐analysis

Abstract: This meta-analysis evaluates the effect of hypnosis in reducing emotional distress associated with medical procedures. PsycINFO and PubMed were searched from their inception through February 2008. Randomized controlled trials of hypnosis interventions, administered in the context of clinical medical procedures, with a distress outcome, were included in the meta-analysis (26 of 61 papers initially reviewed). Information on sample size, study methodology, participant age and outcomes were abstracted independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 57 publications
13
96
0
5
Order By: Relevance
“…The results of this review are partly in line with previous reviews on hypnosis in related patient samples. [41][42][43] A qualitative review on hypnotic analgesia in adults included 2 studies on breast biopsy or cancer surgery and found effects on pain and distress. 43 A meta-analysis on hypnosis for surgery patients concluded that hypnosis can decrease negative affect and pain.…”
Section: Agreements With Prior Systematic Reviewsmentioning
confidence: 99%
“…The results of this review are partly in line with previous reviews on hypnosis in related patient samples. [41][42][43] A qualitative review on hypnotic analgesia in adults included 2 studies on breast biopsy or cancer surgery and found effects on pain and distress. 43 A meta-analysis on hypnosis for surgery patients concluded that hypnosis can decrease negative affect and pain.…”
Section: Agreements With Prior Systematic Reviewsmentioning
confidence: 99%
“…It is generally accepted that hypnotherapy can be used effectively to treat a wide variety of psychological disorders (Alladin & Alibhai, 2007;Craig & Quigley, 2010;Hammond, 2010;Schnur, Kafer, Marcus, & Montgomery, 2008;Stewart, 2005). Maree (2010, p. 354) suggests that hypnotherapy also "offers a distinctive opportunity for enabling people to experience well-being, happiness, comfort, and fulfilment".…”
Section: Hypnotherapy In the 21st Centurymentioning
confidence: 99%
“…On peut alors proposer des produits pharmacologiques tels que des anxiolytiques afin de réduire ce stress, mais ils ont un coût non négli-geable et leurs propres effets secondaires. L'hypnose est une intervention non pharmacologique, dépourvue d'effets secondaires connus, qui a démontré principalement, dans deux méta-analyses [20,21], ses effets bénéfiques pour réduire le stress des procédures médicales. En particulier, une méta-analyse récente, réalisée à partir d'essais contrôlés randomisés, évalue les effets de l'hypnose afin de réduire le stress émotionnel associé aux procédures médi-cales.…”
Section: Intérêt De L'hypnoseunclassified
“…En particulier, une méta-analyse récente, réalisée à partir d'essais contrôlés randomisés, évalue les effets de l'hypnose afin de réduire le stress émotionnel associé aux procédures médi-cales. L'analyse s'étend à de nombreuses procédures, à la fois chirurgicales et non chirurgicales [21]. Les résultats de cette méta-analyse indiquent qu'approximativement 82 % des patients, qui ont subi une procédure médicale avec utilisation de l'hypnose, ont un niveau de stress émotionnel inférieur au groupe témoin.…”
Section: Intérêt De L'hypnoseunclassified